Progress on nuclear reaction rates affecting the stellar production of 26Al. (28th February 2023) - Laird, A M; Lugaro, M; Kankainen, A; Adsley, P; Bardayan, D W; Brinkman, H E; Côté, B; Deibel, C M; Diehl, R; Hammache, F; den Hartogh, J W; José, J; et al.
Abstract: The radioisotope 26 Al is a key observable for nucleosynthesis in the Galaxy and the environment of the early Solar System. To properly interpret the large variety of astronomical and meteoritic data, it is crucial to understand both the nuclear reactions involved in the production of 26 Al in the relevant stellar sites and the physics of such sites. These range from the winds of low- and intermediate-mass asymptotic giant branch stars; to massive and very massive stars, both their Wolf–Rayet winds and their final core-collapse supernovae (CCSN); and the ejecta from novae, the explosions that occur on the surface of a white dwarf accreting material from a stellar companion. Several reactions affect the production of 26 Al in these astrophysical objects, including (but not limited to) 25 Mg( p, γ ) 26 Al, 26 Al( p, γ ) 27 Si, and 26 Al( n, p / α ). Extensive experimental effort has been spent during recent years to improve our understanding of such key reactions. Here we present a summary of the astrophysical motivation for the study of 26 Al, a review of its production in the different stellar sites, and a timely evaluation of the currently available nuclear data. We also provide recommendations for the nuclear input into stellar models and suggest relevant, future experimental work.